In vivo PET/MRI Imaging of the Chorioallantoic Membrane - Gordon Winter; Andrea B. F. Koch; Jessica Löffler; Jessica Löffler; Fedor Jelezko; Mika Lindén; Hao Li; Hao Li; Alireza Abaei; Zhi Zuo; Zhi Zuo; Ambros J. Beer; et al. (Frontiers in Physics, 2020)
The Hen's Egg Test Chorioallantoic Membrane (HET-CAM) of fertilized chick eggs represents a unique model for biomedical research. With its steadily increasing use, non-invasive in ovo imaging for longitudinal direct quantification of the biodistribution of compounds or monitoring of surrogate markers has been introduced. The full range of imaging methods has been applied to the HET-CAM model. From the current perspective, Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) appear promising techniques, providing detailed anatomical and functional information (MRI) and excellent sensitivity (PET). Especially by combining both techniques, the required sensitivity and anatomical localization of the signal source renders feasible. In the following, a review of recent applications of MRI and PET for in ovo imaging with a special focus on techniques for imaging xenotransplanted tumors on the CAM will be provided.